Stability of erythropoietin repackaging in polypropylene syringes for clinical use - Angela Marsili; Giorgia Puorro; Chiara Pane; Anna de Rosa; Giovanni Defazio; Carlo Casali; Antonio Cittadini; Giuseppe de Michele; Brunello Ettore Florio; Alessandro Filla; Francesco Saccà (Elsevier, 2017)
Introduction: Epoetin alfa (Eprex®) is a subcutaneous, injectable formulation of short half-life recombinant human erythropoietin (rHuEPO). To current knowledge there are no published studies regarding the stability of rHuEPO once repackaging occurs (r-EPO) for clinical trial purposes. Materials and methods: We assessed EPO concentration in Eprex® and r-EPO syringes at 0, 60, 90, and 120 days after repackaging in polypropylene syringes. R-EPO was administered to 56 patients taking part in a clinical trial in Friedreich Ataxia. Serum EPO levels were measured at baseline and 48 h after r-EPO administration. Results: No differences were found between r-EPO and Eprex® syringes, but both globally decreased in total EPO content during storage at 4 °C. Patients receiving r-EPO had similar levels in EPO content as expected from previous trials in Friedreich Ataxia and from pharmacokinetics studies in healthy volunteers. Discussion: We demonstrate that repackaging of EPO does not alter its concentration if compared to the original product (Eprex®). This is true both for repackaging procedures and for the stability in polypropylene tubes. The expiration date of r-EPO can be extended from 1 to 4 months after repackaging, in accordance with pharmacopeia rules.